2010
DOI: 10.1087/20100313
|View full text |Cite
|
Sign up to set email alerts
|

Book Reviews

Abstract: The Long Tail: Why the Future of Business is Selling Less of More Chris Anderson Hyperion, 2006, 236 pp. ISBN 104013‐0237‐8, $24.95 Free: The Future of a Radical Price Chris Anderson Hyperion, 2009, ISBN 978‐1‐4013‐2290‐8, $26.95

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Burgess and Green's (2009) early study found that the most popular content on the platform was split in a roughly equal fashion between what they term 'vernacular producers' (amateurs) and commercial producers. But if we consider how the former vastly outnumber the latter, it suggests what tends to be called a long tail distribution: the vast majority of the content produced by vernacular producers achieves little visibility (Anderson 2006). Research on other platforms has similarly found what Rogers (2013: loc 769) describes as a 'tiny ratio of editors to users', often described in terms of a 'power law' (Marres 2017: 148).…”
Section: The Reality Of Online Participationmentioning
confidence: 99%
“…Burgess and Green's (2009) early study found that the most popular content on the platform was split in a roughly equal fashion between what they term 'vernacular producers' (amateurs) and commercial producers. But if we consider how the former vastly outnumber the latter, it suggests what tends to be called a long tail distribution: the vast majority of the content produced by vernacular producers achieves little visibility (Anderson 2006). Research on other platforms has similarly found what Rogers (2013: loc 769) describes as a 'tiny ratio of editors to users', often described in terms of a 'power law' (Marres 2017: 148).…”
Section: The Reality Of Online Participationmentioning
confidence: 99%
“…Both of these papers examine the book industry and assume that book sales can be represented by a power law. It is common for books to be considered as one of the industries where sales follow a power law as described by Anderson (2006) in his bestseller “The Long Tail.”…”
Section: Genesis Of Using Ranks To Predict Salesmentioning
confidence: 99%
“…The search may return a large number of results that require the consumers to look through by reading each product information webpage. When help, such as recommender systems, is available, consumers can more easily find and evaluate the substitute products, thus incurring lower product evaluation costs (Anderson, 2008; Brynjolfsson et al., 2011; De Bruyn et al., 2008).…”
Section: Literature Reviewmentioning
confidence: 99%